(3MeGjI HQGeL GdMGSH GdGdi (B/ s - (3LjgGf aQMGJs; (3MSf YHOGdHGSW LejYi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3GgejI JMbjb GdJhGRf Hjf efTF GdHQGeL heSJNOeg hPdc ef NdGd GdYed ai efXheI hGVMI GdeYGde heMOOI GdGOhGQ dUGdM GdMeGjI GdLOjI GdGcjOI ddHQGeL hGSJNOGeI HhGSWI GdMGFR (B: (3VQhQI GYGOI GdfXQ ai MeGjI GdHQGeL habG dGMcGe Mb GdeDda heOi GYJHGQI eUfa GOHi hHGdJGdi eDda GdHQfGeL hGdPi GWdbJ YdjI GSe (B((3efTF(B) (3GdHQGeL (B: (3GgejI GYGOI GdfXQ ai GdMbhb GdGOHjI GdebQQI dUGMH GdMb Ydi GdHQfGeL hGdPi jYO eUfaG JbfjG YdejG jJZjQ HSQYI aGFbI (B: (3JfXje YedjI GdgfOSI GdYcSjI ddHQGeL s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2009s
(3HHdjhLQGajG(B: (3UaMGJ (B505-512s
Keywords: (3GdbGfhf GdeOfjs; (3GdMQcI GdacQjI ddHQGeLs; (3MeGjI GdHQGeL afjGs; (3MeGjI JcfhdhLjG GdHQGeLs; (3GfhGY HQGeL GdMGSH GdGdjs; (3Mb GdeDdas; (3GdeUfa GdGOHjs; (3GdTQhW GdehVhYjI ddeUfaGJs; (3GdTQhW GdTcdjI ddeUfaGJ s; (3GdMeGjI GdJbfjIs; (3Shb GdHQGeLs; (3JQGNjU GSJZdGd MeGjI HQGeL GdMGSH GdGdj s; (3HQGAI GdGNJQGYs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs